Efficient Order Management: Design and Implementation of a System using Scheduling Algorithms and Expert Validation - Surbakti, Eunike Endariahna; Rizky, Nazim; Pane, Ivransa Zudhi; Khouwira, Filbert (ULTIMATICS, 2023)
This research focuses on the crucial role of system interfaces in enhancing user experience, particularly in the context of an online canteen ordering system. A well-designed interface not only improves user satisfaction but also streamlines the ordering process, addressing issues like queuing in canteens. The study employs Expert Validation to gather valuable insights from experts, ensuring a robust foundation for system development and evaluation. The online canteen ordering system facilitates food orders through an application, eliminating the need for users to physically visit the canteen. This approach not only benefits users but also aids canteen management in efficient order handling.The scheduling algorithms, FCFS (First Come First Served) and SJF (Shortest Job First), are utilized to manage incoming orders. FCFS, chosen for its intuitive handling of queuing problems, complements the SJF algorithm, which excels in efficiently managing numerous orders. The system dynamically switches between these algorithms based on the order load, resulting in an effective queuing structure. Usability testing is conducted to evaluate the system’s user-friendliness, with an impressive average score of 86.6%. This indicates that the system is wellreceived and navigable by users. The website implementation receives an ”good” categorization through UEQ (User Experience Questionnaire) testing, with attractive design and high scores in aspects like Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. These findings collectively affirm the success of the designed interface in delivering a positive user experience for the online canteen ordering system.